The geopolitical factors in the implementation of cluster policies in the AsiaPacific region - V. A. Golovkin; E. A. Pronin; V. V. Tarasenko (Современная наука и инновации)
Geopolitical factors are increasingly significant in the context of cluster strategy development in the countries of the Asia-Pacific region (APR). The study aims to analyze the impact of geopolitics on the development and implementation of cluster policies, as well as to identify key aspects of cluster formation and overcoming challenges in the modern environment. To achieve the set goals, the authors conducted a comprehensive analysis of geopolitical trends in the APR and the effectiveness of cluster initiatives. The research methodology was based on comparing data on the geopolitical situation with indicators of economic cluster development in the region, using both qualitative and quantitative approaches. Significant correlations were identified within the study between geopolitical stability, level of economic development, and the effectiveness of cluster strategies in APR countries. The main success factors included the flexibility of adaptation strategies to changes in the international arena and the ability to overcome political and economic obstacles. The discussion of the results emphasized the importance of considering the geopolitical situation in the development of cluster strategies, as well as the need for alignment of interests among countries in the region for the successful implementation of cluster policies. The research enables researchers, practitioners, and government bodies to interact more actively and develop effective cluster development strategies in the APR, taking into account geopolitical risks and opportunities.